2014
DOI: 10.7314/apjcp.2014.15.13.5299
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Distribution and Epidemiology of Lung Cancer During 2011 in Zhejiang Province of China

Abstract: Background: To explore etiology for providing scientific clues for the prevention of lung cancer. Materials and Methods: Data for lung cancer incidence and meteorological geographic factors from 25 counties in Zhejiang province of China during 2011 were studied. Stepwise multiple regression and correlation analysis were performed to analyze the geographic distribution and epidemiology of lung cancer. Results: 8,291 new cases (5,998 in males and 2,293 females) of lung cancer during 2011 in Zhejiang province wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Soil with high sand content is more likely to produce dust, which is the largest source of PM 2.5 in Zhengzhou (S. Wang et al., 2017 ). NDVI is related to the vegetation cover and greening level of a region, and previous studies have shown that it may affect the occurrence of lung cancer (Lin et al., 2014 ). However, the results of this study showed that the correlation between NDVI and the incidence of lung cancer was not strong.…”
Section: Discussionmentioning
confidence: 99%
“…Soil with high sand content is more likely to produce dust, which is the largest source of PM 2.5 in Zhengzhou (S. Wang et al., 2017 ). NDVI is related to the vegetation cover and greening level of a region, and previous studies have shown that it may affect the occurrence of lung cancer (Lin et al., 2014 ). However, the results of this study showed that the correlation between NDVI and the incidence of lung cancer was not strong.…”
Section: Discussionmentioning
confidence: 99%
“…The study discovered significant variety among different geographic areas and identified areas that were impacted the most by cervical cancer. In another study [27], the investigators used a geographic map to uncover the distribution patterns and risk factors of lung cancer in China. The study discovered two most significant factors contributing to diagnoses of lung cancer, including the poor quality of air and the associated low annual precipitation.…”
Section: Discussionmentioning
confidence: 99%
“…Han et al confirmed that NO 2 emerges as the primary environmental factor influencing lung cancer incidence [ 26 ]. Lin et al discovered that the air quality index and annual precipitation levels affect lung cancer, with high incidence seemingly associated with poor air quality and low yearly precipitation [ 28 ]. Merrill et al observed a reduced risk of developing lung cancer and improved patient survival at high altitudes [ 29 ].…”
Section: Introductionmentioning
confidence: 99%